2004
DOI: 10.1086/422827
|View full text |Cite
|
Sign up to set email alerts
|

A Missense Single-Nucleotide Polymorphism in a Gene Encoding a Protein Tyrosine Phosphatase (PTPN22) Is Associated with Rheumatoid Arthritis

Abstract: Rheumatoid arthritis (RA) is the most common systemic autoimmune disease, affecting approximately 1% of the adult population worldwide, with an estimated heritability of 60%. To identify genes involved in RA susceptibility, we investigated the association between putative functional single-nucleotide polymorphisms (SNPs) and RA among white individuals by use of a case-control study design; a second sample was tested for replication. Here we report the association of RA susceptibility with the minor allele of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

56
1,102
12
20

Year Published

2005
2005
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 1,327 publications
(1,199 citation statements)
references
References 35 publications
56
1,102
12
20
Order By: Relevance
“…29 Furthermore, RNAi experiments have demonstrated that reduced LYP expression in Jurkat's cells occurs concomitantly with an increase in the expression of T-cell receptordependent activation. 25 The downregulatory activity of LYP is mediated as a complex with CSK, which suppresses the T-cell receptor signalling kinases LCK and FYN. Recently, the 1858T allele encoding Trp at amino-acid residue 620 of the PTPN22 gene has been shown to dramatically reduce the binding of LYP to CSK in vitro.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…29 Furthermore, RNAi experiments have demonstrated that reduced LYP expression in Jurkat's cells occurs concomitantly with an increase in the expression of T-cell receptordependent activation. 25 The downregulatory activity of LYP is mediated as a complex with CSK, which suppresses the T-cell receptor signalling kinases LCK and FYN. Recently, the 1858T allele encoding Trp at amino-acid residue 620 of the PTPN22 gene has been shown to dramatically reduce the binding of LYP to CSK in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have associated the 1858T allele with autoimmune diseases [18][19][20][21][22][23][24][25] and generalised vitiligo is thought to have an autoimmune aetiology, 1 although this remains undefined. The frequent association of vitiligo with autoimmune disorders and the demonstration of autoantibodies to melanosomal proteins in the serum of patients with the disease support this theory.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They showed that B‐cells from carriers of this PTPN22 risk allele contained high frequencies of autoreactive clones compared with those from non‐carriers showing how a single polymorphism at one genetic locus can affect the B‐cell repertoire 61. This PTPN22 polymorphism is a gain‐of‐function variant leading to reduced B‐ and T‐cell receptor signalling,62, 63 and has been associated with a range of autoimmune diseases, including RA,64, 65 type 1 diabetes66 and SLE 67. Similar studies on variation in other genes are likely to provide further useful information on how specific biological pathways regulate the B‐cell repertoire.…”
Section: Slementioning
confidence: 99%
“…Ptpn22 encodes the protein LYP, which is an inhibitor of T-cell activation. 24,25 Different allelic variants of Ptpn22 have recently been associated with several autoimmune disorders in humans including RA and Type I diabetes [26][27][28] The upregulation of Tspan-2 and the downregulation of Ptpn22 could indicate a higher activation state of T cells in the congenic strain. This activation might be required for self-reactive T cells to undergo apoptosis or to become T regulatory cells; however, further experiments are needed in order to answer this question.…”
Section: Discussionmentioning
confidence: 99%